2021
DOI: 10.1007/s12094-021-02570-4
|View full text |Cite
|
Sign up to set email alerts
|

A new antisarcoma strategy: multisubtype heat shock protein/peptide immunotherapy combined with PD-L1 immunological checkpoint inhibitors

Abstract: Osteosarcoma, a common malignant tumor in orthopedics, often has a very poor prognosis after lung metastasis. Immunotherapy has not achieved much progress in the treatment because of the characteristics of solid tumors and immune environment of osteosarcoma. The tumor environment is rather essential for sarcoma treatment. Our previous study demonstrated that heat shock proteins could be used as antitumor vaccines by carrying tumor antigen peptides, and we hypothesize that an anti-osteosarcoma effect may be inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The effects of a multi-subtype HSP/peptide vaccine tested in murine osteosarcoma were potentiated by the addition of a PD-L1 inhibitor. The combination triggered elevated cytokine production, stimulated CD4+ and CD8+ T cells and mitigated lung metastasis better than each therapeutic modality alone ( 215 ). Almost all HSP-inhibitors have been administered so far on intermittent dosage schemes.…”
Section: Heat-shock Response and Cancer Immunosurveillancementioning
confidence: 99%
“…The effects of a multi-subtype HSP/peptide vaccine tested in murine osteosarcoma were potentiated by the addition of a PD-L1 inhibitor. The combination triggered elevated cytokine production, stimulated CD4+ and CD8+ T cells and mitigated lung metastasis better than each therapeutic modality alone ( 215 ). Almost all HSP-inhibitors have been administered so far on intermittent dosage schemes.…”
Section: Heat-shock Response and Cancer Immunosurveillancementioning
confidence: 99%
“…Currently, the development of mAbs to block programmed death-1 receptor (PD-1)/programmed death-ligand 1 (PD-L1) has made substantial advances. The related research has been intensively and extensively reviewed. In recent studies, immune checkpoint therapies have shown effectiveness in treating non-squamous cell lung cancer, non-small lung cancer, melanoma, Merkel cell carcinoma, head and neck squamous cell carcinoma, and hepatocellular carcinoma. , For these checkpoint therapies, the expression of PD-L1 is an important biomarker in tissue biopsies. To analyze the immune reaction to PD-1/PD-L1 immune checkpoint treatment, ex vivo biopsy with immunohistochemistry is widely used in the clinic, but it is not appropriate for dynamic monitoring and assessing the PD-L1 heterogeneity.…”
Section: Introductionmentioning
confidence: 99%